2015
DOI: 10.1177/1049909115575709
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of a Meaning-Based Intervention for Patients With Advanced Cancer and Their Spouses

Abstract: Background: Constructing meaning in cancer leads to improved psychosocial outcomes for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 43 publications
0
9
0
11
Order By: Relevance
“…However, studies of whole-person approaches to care in later life have been mainly limited to circumscribed palliative or hospice care at the end of life or for single conditions (eg, cancer). [19][20][21][22][23][24] Much literature on understanding and treating patients with serious illness from a whole-person standpoint has been exploratory, with limited or no follow-up. [23][24][25][26] A smaller number of controlled studies testing multicomponent interventions suggest promising results for quality indicators, family-rated care after death, or quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of whole-person approaches to care in later life have been mainly limited to circumscribed palliative or hospice care at the end of life or for single conditions (eg, cancer). [19][20][21][22][23][24] Much literature on understanding and treating patients with serious illness from a whole-person standpoint has been exploratory, with limited or no follow-up. [23][24][25][26] A smaller number of controlled studies testing multicomponent interventions suggest promising results for quality indicators, family-rated care after death, or quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] Much literature on understanding and treating patients with serious illness from a whole-person standpoint has been exploratory, with limited or no follow-up. [23][24][25][26] A smaller number of controlled studies testing multicomponent interventions suggest promising results for quality indicators, family-rated care after death, or quality of life. [27][28][29] They have generally not focused on improving patient experience.…”
Section: Introductionmentioning
confidence: 99%
“…TACTICs feasibility measures included at least 50% of eligible caregivers enrolling in the study and attendance rates of 70% or greater across the six TACTICs sessions. Acceptability was assessed to be that at least 70% of caregivers enrolled in the study completed the study through T4 and at least 70% of enrolled caregivers reported being mostly to completely satisfied with their experience in TACTICs [45]. The standardized response mean (SRM) effect size for the outcomes was calculated to assess the magnitude of intervention effects at T2, T3, and T4.…”
Section: Discussionmentioning
confidence: 99%
“…Feasibility benchmarks included (1) at least 50% of eligible dyads enrolling in the study and (2) attendance rates of 70% or greater across the 6 sessions. Acceptability benchmarks included (1) at least 70% of participants completing the study 66 and (2) at least 70% of participants reporting being mostly to completely satisfied with their intervention experience. The standardized response mean (SRM) effect size was calculated to assess the magnitude of intervention effects at T2 and T3 for both patients and FCGs separately.…”
Section: Methodsmentioning
confidence: 99%